Ireland to Iberia: Translating Eiléan Ní Chuilleanáin from English to Galician - March, Kathleen (Madrygal. Revista de Estudios Gallegos, 2015)
Translation studies approaches the idea of gender in diverse ways. These include the assignment of gender in the target language, the translation of gender-marked languages, and feminist translation. In this work, we shall study the use or absence of gender markers and the praeterio in the translation of the work by the Irish author Eiléan Ni Chuillanáin. Being a feminist and a nationalist, both feminism and nationalism are consciously and significantly employed in her poems. Looking at various selected examples, we consider it necessary to realise that her texts are being translated into a language which unavoidably establishes gender markers so the translator must always bear in mind the author’s original intent. In order to share the feminist and national perspective of the author, the translator should study her poetic work.